PfSPZ-CVac malaria vaccine demonstrates safety among malaria-experienced adults: A randomized, controlled phase 1 trial. (October 2022) - Coulibaly, Drissa; Kone, Abdoulaye K.; Traore, Karim; Niangaly, Amadou; Kouriba, Bourema; Arama, Charles; Zeguime, Amatigue; Dolo, Amagana; Lyke, Kirsten E.; Plowe, Christopher V.; Abebe, Yonas; Potter, Gail E.; et al.
Summary: Background: Plasmodium falciparum (Pf) Sporozoite (SPZ) Chemoprophylaxis Vaccine (PfSPZ-CVac) involves concurrently administering infectious PfSPZ and malaria drug, often chloroquine (CQ), to kill liver-emerging parasites. PfSPZ-CVac (CQ) protected 100% of malaria-naïve participants against controlled human malaria infection. We investigated the hypothesis that PfSPZ-CVac (CQ) is safe and efficacious against seasonal, endemic Pf in malaria-exposed adults. Methods: Healthy 18–45 year olds were enrolled in a double-blind, placebo-controlled trial in Bougoula–Hameau, Mali, randomized 1:1 to 2.048 × 10 5 PfSPZ (PfSPZ Challenge) or normal saline administered by direct venous inoculation at 0, 4, 8 weeks. Syringes were prepared by pharmacy staff using online computer-based enrolment that randomized allocations. Clinical team and participant masking was assured by identical appearance of vaccine and placebo. Participants received chloroquine 600mg before first vaccination, 10 weekly 300mg doses during vaccination, then seven daily doses of artesunate 200mg before 24-week surveillance during the rainy season. Safety outcomes were solicited adverse events (AEs) and related unsolicited AEs within 12 days of injections, and all serious AEs. Pf infection was detected by thick blood smears performed every four weeks and during febrile illness over 48 weeks. Primary vaccine efficacy (VE) endpoint was time to infection at 24 weeks. NCT02996695. Findings: 62 participants were enrolled in April/May 2017. Proportions of participants experiencing at least one solicited systemic AE were similar between treatment arms: 6/31 (19.4%, 95%CI 9.2-36.3) of PfSPZ-CVac recipients versus 7/31 (22.6%, 95%CI 29.2-62.2) of controls ( p value = 1.000). Two/31 (6%) in each group reported related, unsolicited AEs. One unrelated death occurred. Of 59 receiving 3 immunizations per protocol, fewer vaccinees (16/29, 55.2%) became infected than controls (22/30, 73.3%). VE was 33.6% by hazard ratio ( p = 0.21, 95%CI -27·9, 65·5) and 24.8% by risk ratio ( p = 0.10, 95%CI -4·8, 54·3). Antibody responses to PfCSP were poor; 28% of vaccinees sero-converted. Interpretation: PfSPZ-CVac (CQ) was well-tolerated. The tested dosing regimen failed to significantly protect against Pf infection in this very high transmission setting. Funding: U.S. National Institutes of Health, Sanaria. Registration number: ClinicalTrials.gov identifier (NCT number): NCT02996695.